Cultural tourism as a professional opportunity in academic degree in tourism: Degree in Tourism and Heritage Education - Fernández-Laso, María Cristina; López Ronco, María Ángeles (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The main objective of this paper is to establish whether an academic degree in tourism from the public universities of the Community of Madrid provides optimal training to works as a cultural tourism professional. The methodology focuses on analysis of the curricula of tourism degrees offered by Madrid’s public universities and structured interviews with 20 university teachers. The results show that the university curricula have insufficient training in cultural heritage teaching and that more is necessary for students to perceive it as a professional opportunity.